β-noradrenergic receptor activation specifically modulates the generation of sighs in vivo and in vitro - Viemari, Jean-Charles; Garcia, Alfredo I.; Doi, Atsushi; Elsen, Gina; Ramirez, Jan Marino (Frontiers in Neural Circuits, 2013)
The pre-Bötzinger complex (preBötC), an area that is critical for generating breathing (eupnea), gasps and sighs is continuously modulated by catecholamines. These amines and the generation of sighs have also been implicated in the regulation of arousal. Here we studied the catecholaminergic modulation of sighs not only in anesthetized freely breathing mice (in vivo), but also in medullary slice preparations that contain the preBötC and that generate fictive eupneic and sigh rhythms in vitro. We demonstrate that activating -noradrenergic receptors (B-NR) specifically increases the frequency of sighs, while eupnea remains unaffected both in vitro and in vivo. B-NR activation specifically increased the frequency of intrinsically bursting pacemaker neurons that rely on persistent sodium current (INap). By contrast, all parameters of bursting pacemakers that rely on the non-specific cation current (ICAN) remained unaffected. Moreover, riluzole, which blocks bursting in INap pacemakers abolished sighs altogether, while flufenamic acid which blocks the ICAN current did not alter the sigh-increasing effect caused by B-NR. Our results suggest that the selective B-NR action of sighs may result from the modulation of INap pacemaker activity and that disturbances in noradrenergic system may contribute to abnormal arousal response. The B-NR action on the preBötC may be an important mechanism in modulating behaviors that are specifically associated with sighs, such as the regulation of the early events leading to the arousal response.